Larangan Shalat dalam Keadaan Mabuk dalam Perspektif Ushul Fiqh: Kajian atas Q.S. An-Nisa: 43 melalui Ijma’ dan Qiyas - Lidia Yati Sofiana; Ersa Nur Khasanah (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
The prohibition of performing prayer in a state of intoxication as stated in Q.S. An-Nisa verse 43 emphasizes the importance of full awareness in worship and serves as the basis for the validity of prayer, namely maintaining both physical and spiritual purity. Although the Qur’an does not provide a detailed explanation regarding other forms of intoxicating substances, particularly in the contemporary era, this study—through the ushul fiqh approach using the methods of ijma’ (consensus) and qiyas (analogy)—finds that ijma’ affirms the obligation to maintain awareness as an absolute requirement agreed upon by scholars, while qiyas extends the relevance of the law to include modern intoxicants such as narcotics and prohibited drugs. Thus, ijma’ functions to strengthen legal authority, while qiyas ensures the flexibility and relevance of Islamic law in addressing the challenges of modern times, making ushul fiqh a vital foundation for preserving the continuity of sharia principles while providing solutions to contemporary issues.